Stock market liberalization, returns and integration in Asia / Noor Azryani Auzairy - Auzairy, Noor Azryani (2014)

(untitled)
The government authorities and policy makers of four Asian countries, specifically, Malaysia, Thailand, Indonesia and South Korea, have been continuously introducing and implementing stock market liberalization policies subsequent to its first official implementation. The first official stock market liberalizations of those badly affected Asian countries by the 1997 Asian financial crisis, were enforced in late 1980s or early 1990s. Malaysia, Thailand, Indonesia and South Korea, decided to continuously liberalize their stock markets to the foreign investors by increasing the percentage of foreign ownership in local equities. This work aims to determine whether an increase in the percentage of foreign ownership in local equities, would provide any impact on stock market returns of those four Asian countries. The level of stock market integration post liberalizations between the Asian countries and the world (MSCI-World Index) are also investigated The subsequent stock market liberalization considered in this work is from 1997, the start of the Asian financial crisis, to 2009, the year of the U.S. subprime mortgage crisis.. To examine the impact of stock market liberalizations on its returns, multivariate ordinary least square regression analyses are utilized, with controlling for the effects of stock market characteristics and macroeconomic fundamentals. The four countries stock market returns are measured based on countries’ main and sector stock indices. Controlling for the effects of stock market characteristics and macroeconomic fundamentals, stock market size, liquidity and volatility are used as proxies to stock market characteristics, while the proxies for macroeconomic fundamentals include exchange rates, interest rates and oil prices. This study also applies coefficient correlation, regression analyses, cointegration tests, and vector autoregressive models (VAR) to test the degree of stock market integration in the short-run and long-run, between the four Asian countries and the world market (MSCI World index). The empirical findings from this work reduce the confidence that subsequent stock market liberalizations would significantly improve the stock market returns. This work, however, does not agree that subsequent stock market liberalization is ineffective in affecting stock market returns. As controlled variables, both stock market characteristics and macroeconomic fundamentals have lack of support for the robustness of the results on the significant impact of the variables on stock market returns. There is weak evidence of longrun stock market integration for the four countries and the world market. However, results reveal that there is short run integration. In summary, this work focuses on the impact of subsequent liberalization of the stock market implemented from 1997 onwards, which distinguishes it from previously available literature, mostly concerning the first official stock market liberalization. Empirical findings from this work would assist policy makers in determining future strategies on liberalization, whether should there be greater liberalization or greater regulation to be implemented. This would enable international portfolio investors to make proper assets allocation choices. The firms’ shareholders and the public would also be able to forecast the effects of future stock market liberalization policies.